Analisis Strategi Bisnis Pada BSI KCP Cilacap Kroya Dengan Menggunakan Metode Space Matrix Untuk Menentukan Posisi Strategi Perusahaan - Gita Rahmayanti; Isnaeni Laela Wahyuningsih; Nur Fadilah Rakhmawati; Syifa Himatul Hasanah; Yoiz Shofwa Shafrani (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study aims to analyze the business strategy implemented by Bank Syariah Indonesia KCP Cilacap Kroya by utilizing the Strategic Position and Action Evaluation Matrix (SPACE) method. The method used in this study is descriptive qualitative, with data collection techniques in the form of observation, interviews, and documentation. The analysis is carried out through four main dimensions in the SPACE Matrix, namely Financial Strength (FS), Competitive Advantage (CA), Industry Strength (IS), and Environmental Stability (ES). The findings of this study indicate that Bank Syariah Indonesia KCP Cilacap Kroya is in Quadrant I (aggressive) with coordinates X of 1.25 and Y of 1.5. This position indicates that the institution has solid internal strength and many external opportunities for growth. Strategies that can be implemented include market penetration, market development, digital technology modernization, improving the quality of human resources, and diversifying products and services in accordance with sharia principles. By implementing this strategy, it is hoped that BSI KCP Cilacap Kroya can increase its competitiveness, expand its market share, and strengthen its presence in the Islamic banking sector in Cilacap and its surroundings.